PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PEMERIKSA KEUANGAN PROVINSI BALI - Ni Putu Litamara Yoga Padma Sari; Ni Luh Sili Antari (Journal Research of Management, 2020)
This study aims to determine the effect of emotional intelligence on the performance of BPK Representative Bali employees, find out the influence of work stress on employee performance on BPK Representative Bali, find out the influence of emotional intelligence and work stress on employee performance on BPK Perwakila Bali. In this study, the sample used was the employee of BPK Representative Bali. The sampling technique in this research uses nonprobability sampling technique, which is saturated sampling. The number of respondents used in this study is 100 respondents. The analysis technique used in this study is multiple linear regression analysis with hypothesis testing using the t test. The results showed that emotional intelligence affected the performance of employees at the Bali Representative BPK and work stress negatively affected the performance of employees at the Bali Representative BPK. Emotional intelligence partially has a positive and significant influence on employee performance (Y), which can be seen in the regression coefficient b₁X₂. Emotional intelligence (X₁) and work stress (X₂).